Does pricing carbon mitigate climate change? Firm-level evidence from the European Union emissions trading scheme - Jonathan Colmer; Ralf Martin; Mirabelle Muûls; Ulrich J. Wagner (National Bank of Belgium, 2023)
In theory, market-based regulatory instruments correct market failures at least cost. However, evidence on their efficacy remains scarce. Using administrative data, we estimate that, on average, the EU ETS - the world's first and largest market-based climate policy - induced regulated manufacturing firms to reduce carbon dioxide emissions by 14-16% with no detectable contractions in economic activity. We find no evidence of outsourcing to unregulated firms or markets; instead firms made targeted investments, reducing the emissions intensity of production. These results indicate that the EU ETS induced global emissions reductions, a necessary and sufficient condition for mitigating climate change. We show that the absence of any negative economic effects can be rationalized in a model where inattentive firms underinvest in energy-saving capital prior to regulation. Guided by the predictions of this model, we classify firms with low initial productivity or high energy intensity as potentially inattentive. We estimate larger reductions in emissions and increases in economic activity for those firms, consistent with regulation-induced cost savings or efficiency increases.
Keywords: Q54 Q58; H23; L50; F18; 330; cap-and-trade; carbon leakage; investment; climate policy